Motor-Enriched Encoding Can Improve Children’s Early Letter Recognition - Damsgaard, Linn; Elleby, Sofie Rejkjær; Gejl, Anne Kær; Malling, Anne Sofie Bøgh; Bugge, Anna; Lundbye-Jensen, Jesper; Poulsen, Mads; Nielsen, Glen; Wienecke, Jacob (Frontiers in Psychology, 2020)
It is not known how effective specific types of motor enriched activities are improving academic learning and early reading skills in children. The aim of this study was to investigate whether fine or gross motor enrichment during a single session of recognizing letters ‘b’/’d’ can improve within-session performance or delayed retention the following day in comparison to letter recognition practice without movement. Furthermore, the aim was to investigate children’s motivation to perform the specific tasks. A randomized, controlled, intervention study investigated the effect of 10-minute motor enriched ‘b’/’d’ letter training on children’s ability to recognize the letters ‘b’ and ‘d’ (n = 127, mean age = 7.61± SD = 0.44 years) acutely, and in delayed retention tests. Three groups were included: a fine motor enriched group (FME), a gross motor enriched group (GME), that received 10 minutes of ‘b’ and ‘d’ training with enriched gestures (fine or gross motor movements) and a control group (CON), which received non-motor enriched ‘b’/’d’ training. The children’s ability to recognize ‘b’ and ‘d’ were tested before (T0), immediately after (T1) and one day after the intervention (T2). The children’s motivation for the training was investigated at T1. FME improved their ability to recognize ‘b’/‘d’ from T1 to T2 (p = 0.02) and FME improvement was greater compared to GME (p = 0.02) and CON (p = 0.03) at T2. Children’s mean reaction time at correctly identified ‘b’ and ‘d’ was improved for GME from T0 to T1 (p = 0.001). From T1 to T2 both FME and GME improved their mean reaction time (p < 0.01, p = 0.01). The children’s motivation-score was greater for FME and GME compared to CON (FME-CON: p = 0.01; GME-CON: p = 0.01). The study demonstrated that fine motor enriched training improved children’s letter recognition more than gross motor enriched and non-motor activities one day after training. Furthermore, fine and gross motor training improved children’s mean reaction time and motivation in contrast to non-motor training. The study provides a new method for letter learning and future research should investigate the underlying mechanisms.